2007
DOI: 10.1287/mnsc.1060.0624
|View full text |Cite
|
Sign up to set email alerts
|

Interfirm Collaboration Networks: The Impact of Large-Scale Network Structure on Firm Innovation

Abstract: The structure of alliance networks influences their potential for knowledge creation. Dense local clustering provides information transmission capacity in the network by fostering communication and cooperation. Nonredundant connections contract the distance between firms and give the network greater reach by tapping a wider range of knowledge resources. We propose that firms embedded in alliance networks that exhibit both high clustering and high reach (short average path lengths to a wide range of firms) will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
869
1
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,216 publications
(950 citation statements)
references
References 56 publications
27
869
1
24
Order By: Relevance
“…This has resulted in a growing body of literature aimed at understanding inter-firm networks in general and their effects on firm performance (Gulati, 1995(Gulati, , 1998Sorenson and Stuart, 2001;Rosenkopf and Schilling, 2007;Schilling and Phelps, 2007).…”
Section: Sector-level Studiesmentioning
confidence: 99%
“…This has resulted in a growing body of literature aimed at understanding inter-firm networks in general and their effects on firm performance (Gulati, 1995(Gulati, , 1998Sorenson and Stuart, 2001;Rosenkopf and Schilling, 2007;Schilling and Phelps, 2007).…”
Section: Sector-level Studiesmentioning
confidence: 99%
“…The logic of alliance formation is a network, not merely a dyadic or nodal (firm-level), one. The positioning of the partners; the availability of third party ties; the macro-structural properties of the network such as clustering and connectivity-all have been shown to condition the formation of new ties (Schilling and Phelps 2007). As Gulati (1998) suggests, such patterns are counter-intuitive.…”
Section: Introductionmentioning
confidence: 99%
“…Research on 'small world' properties of large scale networks has shown complementary benefits in network topographies that combine embeddedness and sparseness (Schilling and Phelps, 2007;Uzzi and Spiro, 2005).…”
Section: Triplet Value Estimation Methods With Three Different Types Omentioning
confidence: 99%